Analysis of Services on wait and Time Patient Satisfaction in Prof. dr. Soekandar Hospital - Mas'ulun Mas'ulun (Journal for Quality in Public Health, 2019)
Patient satisfaction is the main thing that a hospital needs to prioritize in order to survive compete and maintain wahat has happened because the hospital is a business entity engaged in health services. This type of research is quantitative research with observational analytic design with cross-sectional approach. The sample size in this study is 103 respondents taken by simple random side. Data were collected using questionnaires and observation sheets, then analyzed using logistic regression test Simultaneously administration, medical and pharmacy services have a significant effect on waiting time with Sig 0.005 <0.0. while partially only administrative service variables that affect the waiting time with a p-value of 0.036 <α = 0.05. Taken together the administrative services (x1) of medical services (x2) and pharmacy services (x3) are not related to Satisfaction (Y2). While partially there is no effect on satisfaction variables. There is a significant influence between waiting time and patient satisfaction. The results show that if the waiting time is fast then the patients will tend to be 9,435 times more likely to be satisfied. Satisfaction is greatly influenced by waiting time, therefore the hospital must always innovate by utilizing technology to shorten patient waiting time. shorten patient waiting time